Designing reverse logistics network of end-of-life-buildings as preparedness to disasters under uncertainty - Aydin, Nezir (ELSEVIER SCI LTD, 2020)
Preparedness as a fundamental disaster management stage, aims to rise the chance of victims to survive. Further, the reconstruction of the end-of-life-buildings is the vital step for the preparedness to earthquakes. Therefore, this study aims to mitigate the effect of earthquakes by reconstructing end-of-life-buildings and developing plans on recycling the debris occurs during the demolition processes. Since Turkey survived several earthquakes, the government started a project to reconstruct end-of-lifebuildings located on the seismically active zones. With this motivation, a stochastic MILP model is developed to design a reverse logistic network for end-of-life-buildings' debris. In the worst case, in total, 447063915 tons of debris is anticipated to occur, and 20 different cases are developed and analyzed to determine the best plan for Istanbul. Based on the results and sensitivity analysis, the best strategy is determined as setting up an extra landfilling area and transferring 80% of the debris from demolition sites to recycling centers and increasing the capability of the recycling centers to be able to process 90% of the debris arrive at the centers. By applying this strategy, the costs could be reduced by 98%. The developed framework is the first study that considers debris management as a preparedness stage to earthquakes, and the proposed model is easily can be applied to any region in the world, given that the parameters are revised because each region or country has its unique dynamics. (c) 2020 Elsevier Ltd. All rights reserved.
Keywords: Debris; Recycling; Earthquake; Stochastic MILP; End-of-life-buildings; Disaster; DEMOLITION WASTE MANAGEMENT; CONSTRUCTION; MODEL; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology